Covid-19 Pandemic and ICT Performance in Nigerian Banks: Financial Transaction Perspective - Frances Nwamaka Madu; Audu Tanimu; Vincent Onodugo; Ejikeme Isichei (International Journal of Entrepreneurship, Business, and Creative Economy, 2023)
The global outbreak and spread of coronavirus disease (COVID-19) have been referred to as the most dangerous pandemic since World War II. The speed of the spread and the severity of the damage caused by the virus has traumatized the global economy affecting both banks and customers. With the lockdown imposed by the government to restrict the movement of people and activities caused by the increased level of coronavirus cases in Nigeria, the fate of the financial users of about 40 million became unknown. Given the analysis of data on trends of COVID-19 infections from the World Health Organization and Nigerian Centres for Disease Control and Prevention, the study assessed the current situation. It indicated some specific concepts that the banking sector should consider and address while taking the necessary measures to cope with the new change. The study used an ex-post-facto research design, enabling the researcher to measure the effect or relationship between the dependent variable and explanatory variables using time-series secondary data. The data collected was reviewed, and validated by CBN, the Nigeria Bureau of Statistics, and the Nigerian Inter-Bank Settlement System (NIBSS) websites. The study concluded that the ICT volume of e-payment has no significant effect on operational efficiency in Nigeria Banks, and the ICT value of e-payment significantly affects operational efficiency in Nigeria Banks during the coronavirus lockdown.